2015
DOI: 10.1080/08856257.2015.1023001
|View full text |Cite
|
Sign up to set email alerts
|

Hope, optimism and loneliness among first-year college students with learning disabilities: a brief longitudinal study

Abstract: The goals of the study were to examine personal resources and social distress during the first month in college among students with learning disabilities (LD) and to compare their experiences with non-LD peer. The sample consisted of 335 first-year undergraduate students falling into two groups: 85 students with LD and 250 non-LD students. Questionnaires assessed hope, dispositional optimism and loneliness. We hypothesised that, after participation in a single-session hope intervention workshop, the hope and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
1
18
0
2
Order By: Relevance
“…Intervention studies have shown that hope can be enhanced through various approaches (Cheavens, Feldman, Gum, Michael, & Snyder, ; Feldman & Dreher, ; Marques, Lopez, & Pais‐Ribeiro, ). Yet students with LD may require extended support in order to maintain the impact of hope‐based intervention (Rosenstreich, Feldman, Davidson, Maza, & Margalit, ). Future work should address ways of altering existing interventions for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies have shown that hope can be enhanced through various approaches (Cheavens, Feldman, Gum, Michael, & Snyder, ; Feldman & Dreher, ; Marques, Lopez, & Pais‐Ribeiro, ). Yet students with LD may require extended support in order to maintain the impact of hope‐based intervention (Rosenstreich, Feldman, Davidson, Maza, & Margalit, ). Future work should address ways of altering existing interventions for this population.…”
Section: Discussionmentioning
confidence: 99%
“…We also focused on enjoyment, as it has been suggested as a particularly important academic emotion among primary school students (Ahmed, van der Werf, Kuyper, & Minnaert, 2013). In addition, we focused on hope, which can be assumed to be a relevant emotion among students with LD, as struggles often characterize their academic lives (Lackaye, Margalit, Ziv, & Ziman, 2006; Orly & Margalit, 2014; Rosenstreich, Feldman, Davidson, Maza, & Margalit, 2015). Furthermore, as reading and math difficulties have separate profiles (Landerl et al, 2009; Willcutt et al, 2013), and academic emotions have been shown to be domain specific (Goetz, Frenzel, & Pekrun, 2006), we examined both reading difficulties (RD) and math difficulties (MD) and their relationship to subject-specific academic emotions.…”
Section: Ld and Academic Emotionsmentioning
confidence: 99%
“…Atienza et al () found that problems at work predicted decreasing optimism scores in adult women. Rosenstreich and colleagues (Rosenstreich, Feldman, Davidson, Maza, & Margalit, ) reported lower optimism among first‐year college students with learning disabilities compared to those without learning disabilities. Segerstrom () investigated whether resource growth influences the optimism of graduates from law school and suggested that increases in social networks (i.e., a higher number of friends) predicted subsequent increases in optimism.…”
Section: Introductionmentioning
confidence: 99%